Intercultural perspectives on research writing - Mur-Dueñas, Pilar; Ŝinkūi̇enė, Jolanta (AILA applied linguistics series ;, 2018)
This volume offers a fresh intercultural perspective on the discursive and rhetorical challenges non-Anglophone scholars face while writing and publishing in English for an international readership. The volume presents a wide spectrum of text-based intercultural analyses of academic texts written in L2 English. Placed in the context of a rapidly increasing role of English as the universal language of scientific and scholarly communication, the contributions included attempt to explore the native language influence on L2 English academic texts or, conversely, the influence of rhetorical or discursive features of English on L2 texts. Spanning from texts by Chinese to Lithuanian authors, the chapters in this volume offer a rich selection of lexico-grammatical, discursive and rhetorical elements analysed and compared across genres, disciplines and languages both within synchronic and diachronic perspectives. This volume will be of interest to both experienced and novice researchers in such fields as English for Academic Purposes, Intercultural Rhetoric, Genre Theory, Corpus Linguistics, and English as a Lingua Franca.